Opportunities for enhancing poor women’s socioeconomic empowerment in the value chains of three African non-timber forest products (NTFPs) - Shackleton, S.; Paumgarten, F.; Kassa, H.; Husselman, M.; Zida, M. (2011)
The value chains of three internationally important dry forest NTFPs, namely gum arabic, gum olibanum (frankincense) and honey from Burkina Faso, Ethiopia and Zambia respectively, were assessed in terms of the roles played by women and the benefits they obtain from their involvement. Women perform a variety of functions at different stages in the value chains, but their roles tend to be poorly visible and inadequately acknowledged, largely because they are either operating in the informal sector, are part-time employees, or carry out their activities at home between family responsibilities. Where women’s roles are more prominent, this is primarily due to gender orientated interventions by external agencies. Several constraints to fostering women’s empowerment were identified, with some easier to overcome than others. Particularly difficult to address are gender based, social-cultural barriers. Suggestions for enhancing women’s benefits include: greater recognition of informal markets, the opportunities and constraints associated with them, and their position relative to export markets; improved support for collective action where this can provide women with greater voice, negotiating power, and help with economies of scale; more targeted training that addresses areas identified by women as useful and important to them; time-saving technologies and support systems such as child care; and creating greater gender awareness amongst stakeholders.